Current Pharmacological Treatment for Sleep Disorders in Children and Adolescents with Autism Spectrum Disorder - Altun, Hatice; Cömertoğlu Arslan, Semiha (European Journal of Therapeutics, 2024)
Sleep disorders are very common in children and adolescents with Autism Spectrum Disorder (ASD) and can negatively impact their lives, mental health, developmental processes, families' lives, and emotional well-being. It is essential to determine the specific sleep disorder and its underlying cause in treatment planning. Currently, nonpharmacological and pharmacological interventions are the main treatments for improving sleep disorders in children and adolescents with ASD. If nonpharmacological strategies are unsuccessful or difficult to implement, medications should be considered and used in conjunction with them. Melatonin, behavioral interventions, and parent education are the most effective treatments to improve sleep, relative to other pharmacological treatments. Medications used to treat sleep disorders in these children are used off-label. Melatonin appearing to be safe and effective may be an evidence-based and efficacious first-line treatment for treating insomnia symptoms in children and adolescents with ASD. Antipsychotics (e.g.low dose quetiapine), antidepressants with strong sedative effects such as trazodone and mirtazapine, antihistamines (e.g.diphenhydramine, niaprazine), alpha-adrenergic drugs (e.g. clonidine), benzodiazepines (e.g.clonazepam) and other hypnotic drugs, anticonvulsants (e.g. gabapentin), Alzheimer's drugs (e..g donepezil), superoxide and iron treatment are other drugs used in pharmacological treatment. Depending on the type of sleep disorders and the presence of comorbidities, the most effective pharmacological treatment should be selected on a case-by-case basis.